Interdependencies and reciprocity of private and common property resources in the Central Karakorum - Schmidt, Matthias (ERDKUNDE, 2004)
Agricultural and pastoral lands as well as water which can be used for irrigation are essential resources for the combined mountain agriculture which is practiced by the population of the Central Karakorum; due to their limited availability they are managed in a strict manner. The assumption - made in the debate about the Tragedy of the Commons - that common utilisation of resources necessarily leads to their degradation is challenged. Taking the example of Shigar in Baltistan (Northern Pakistan) current patterns of utilisation for land and water resources, their governing institutions such as water and pasture rights as well as regulations for land tenure and land alienation are presented. It will be shown that autochthonous management strategies and institutions, which are still able to maintain a complex network of irrigation canals, to ensure just access to the resources, to resolve conflicts internally and to apply regulations flexibly, are proving to be very robust and capable of facilitating sustainable resource utilisation.